Neolinoptes gen. n., a replacement name for the net-winged beetle genus Linoptes Gorham, 1884 and a new species of Lycomorphon from Guyana (Coleoptera: Lycidae) - Nascimento, Elynton Alves Do; Bocakova, Milada (Zootaxa, 2017)
Neolinoptes gen. n. is erected to replace Linoptes Gorham, 1884, preoccupied by Linoptes Menge, 1854 (Arachnida: Araneae). Consequently, Neolinoptes imbrex (Gorham, 1884) comb. n., N. amazonicus (Pic, 1923) comb. n., N. atronotatus (Pic, 1922) comb. n., N. atripennis (Pic, 1932) comb. n. are proposed. Calocladon rubidum Gorham, 1884 is transferred to Neolinoptes. Lycomorphon iwokrama sp. n. is proposed as new to science and the genus is recorded from Guyana for the first time. Additionally, Falsocaenia irregularis var. germaini Pic, 1931 is elevated to species rank and past confusion on F. irregularis discussed. New data on geographical distribution of Falsocaenia paranana (Pic, 1922) are presented.